Konsekuensi Betrayal Trauma Pada Individu Yang Mengalami Pengkhianatan Dalam Hubungan Pacaran - Okta Istiawati; Ulfa Amalia (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
Betrayal trauma is a condition of pain experienced by a person after receiving bad treatment from people who are trusted. This research is motivated by the problem of indications of betrayal trauma due to cases of betrayal in dating relationships. The purpose of this study is to determine the empirical picture of individuals who experience betrayal in dating relationships and how the impact caused by betrayal trauma both physically and psychologically. This research method uses descriptive qualitative method. Data collection uses interview techniques and the IES-R test. The main subjects were 6 individuals aged 18-25 years. The results showed that the empirical picture of individuals due to betrayal trauma caused fear in interacting and establishing relationships, especially with the opposite sex. Physical consequences include difficulty concentrating, difficulty sleeping, loss of appetite, weight loss, stomach illness, and behavioural changes. Psychological consequences include difficulty in rebuilding trust, numbness/anger, anxiety, alexithymia, dissociation, and anxiety. This research is expected to provide new insights so that it can be used to provide effective guidance and therapy due to betrayal trauma. Suggestions for future researchers can develop research variables such as identifying factors that cause betrayal trauma, the effects of betrayal trauma, and strategies to overcome betrayal trauma independently.